PROGRAM GURU PENGGERAK SEBAGAI SUMBER BELAJAR - Faiz, Aiman; Faridah, Faridah (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2022)
The driving teacher program is believed to be able to provide a stimulus for teachers to be able to develop better, referring to Pancasila values. The purpose of this article is to describe and explore the various concepts that form the basis of thought and main ideas in the teacher mobilization program. With this aim, the research methodology used is library research. The results of the study explain that entering the 21st century learning concept, Indonesian education needs to reconstruct the educational paradigm so that it can continue to exist in the midst of this globalized education era. The driving teacher program is one of the solutions implemented by the Minister of Education and Culture to prepare for this. The driving teacher program can develop skills for the required pedagogy, the driving teacher is also directed at managerial abilities to be able to become leaders, be it principals, supervisors or leaders in the class itself. Thus, the role of the driving teacher is one of the efforts to develop learning in the 21st century in order to produce graduates who are superior and have a student profile of Pancasila.